Innovation and standards in clinical practice: The case of HIV treatments - Monica Merito; Andrea Bonaccorsi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2005)
The goal of this study was to analyze the emergence of treatment standards associated with the adoption of anti-HIV drug innovations in the empirical setting of Italian clinical practice. Due to the rapid pace of technological change and the initial uncertainty concerning capabilities and indications of new treatments, the emergence of standard patterns of care turned out to be far from predictable and straightforward. Health providers' links to an international medicine and their internal coordination mechanisms were found to be associated with clinical decisions. Effectiveness and health costs of diverging treatment strategies were also compared.
Keywords: 330; Gesundheitsversorgung; AIDS; Innovation; Gesundheitskosten; Italien